The Impact of Video-Assisted Debriefing on Fostering Self-Critical Thinking in Mental Health Nursing Students - León-Campos, Álvaro; Quemada-González, Casta; Gutiérrez-Rodríguez, Laura del Carmen; Pérez-Ardanaz, Bibiana; García-Mayor, Silvia; Kaknani-Uttumchandani, Shakira; Martí-García, Celia (Wiley, 2025)
This study investigated the impact of video recordings from simulated mental health scenarios on the self-critical thinking of undergraduate nursing students. Video-assisted debriefing (VAD) enables students to review their own performance, clarifying memory gaps, applying theory to practice, and fostering self-reflection to identify strengths and areas for improvement. Although widely used, few studies have examined its effect specifically on self-critical capacity in mental health nursing education. A quasi-experimental exploratory design was used, collecting both quantitative and qualitative data after two debriefing formats: verbal and video-assisted. Quantitative data tracked trends in self-evaluation, while qualitative data explored students' reflections on performance, emotions, strengths, and weaknesses. Data integration provided comprehensive insight. Quantitative results showed no significant changes between the two evaluation moments. However, qualitative analysis revealed deeper reflections and stronger identification of strengths during VAD sessions. Students felt more self-aware and critical when watching themselves, recognizing specific areas for improvement and reporting enhanced emotional insight. VAD proved valuable in developing students’ self-perception and reflective thinking in mental health simulations. Some mental health care aspects remained difficult regardless of feedback type, suggesting the need for focused training. Mixed-method approaches offered richer understanding of learning processes. Implications for Nursing Management: Incorporating VAD into clinical training can enhance studen
Keywords: Enfermería; Salud mental; Métodos de simulación; Estudiantes - Salud e higiene; Debriefing; Mental health; Nursing education; Self-assessment; Simulation training